Confronting Canada’s overdose crisis: what’s the deal with decriminalization? - Seliga, Rebecca (University of Ottawa Journal of Medicine, 2022)
The current overdose epidemic in Canada has only been exacerbated by the COVID-19 pandemic. Deaths from overdose are increasing, and urgent response and action are needed to save the lives of people who use drugs. The concept of ‘decriminalizing drugs’ is not new, but discourse around it has been increasing recently, with major urban centres calling on the Canadian government to take action. This commentary discusses the meaning of decriminalization, recent progress that has been made in Canada, and its possible implications on the lives of people who use drugs.